A world of art - Sayre, Henry M., 1948- (Boston : Prentice Hall, 2012)
"Henry Sayres art appreciation text, The World of Art, is an amazing introduction to the world of art. Students with little background in the arts routinely reach out to Henry to share how the text has influenced their lives. This is so meaningful because Henrys inspiration for A World of Art was his own students. His students wanted to see themselves reflected in their textbook. Henry decided to write an art appreciation textbook that represented all artists, not just the Western canon found at that time in the other texts. He also created a text that fostered critical thinking through looking at, talking about, and questioning works of art for his students. The result was A World of Art and the new seventh edition continues to build on those two themes- coverage of contemporary global art and a strong critical thinking framework throughout the text. This edition includes new ways for students to experience art with the new MyArtsLab, which includes ART 21 videos, Discovering Art simulations, Closer Look tours, and an eText of Writing about Art, also by Henry Sayre." --
Part 1: The visual art. A world of art ; Developing visual literacy ; Seeing the value in ar t-- Part 2: The formal elements and their design. Line ; Space ; Light and color ; Other formal elements ; The principles of design -- Part 3: The fine arts media. Drawing ; Printmaking ; Painting ; Photography and time-based media ; Sculpture ; The crafts as fine art ; Architecture ; The design profession -- Part 4: The visual record : placing the arts in historical context. The ancient world ; The age of faith ; The Renaissance through the Baroque ; The eighteenth and nineteenth centuries ; From 1900 to the presen t-- The critical process -- Glossary.
Includes index.
Includes bibliographical references and index.
Keywords: Art; Art -- Textbook